ANALISIS KEBIJAKAN DIVIDEN DAN KEMAMPULABAAN TERHADAP NILAI PERUSAHAAN (Studi Kasus pada PT. Tambang Bukit Asam Tbk. dan PT. Timah Tbk.) - Yuli Anwar (Jurnal Ilmiah Binaniaga, 2011)
Intention of research this is the to know dividend policy relation to company value, to know relation profitability to company value and know dividend policy relation and profitability with in simultaneous to company value. Method of analysis and relation measurement and influence between variable in this research by using correlation coefficient, determinant coefficient and regression coefficient. Research Result this is the (a) Dividend policy with proxy dividend per share have relation and influence significant to company value with proxy stocks market value at PT Timah Tbk by significant level 0,0151. but at PT Tambang Bukit Asam Tbk not haves relation and influence significant by significant level 0.4448, caused by factor external that is unfavourable economy condition. b) Profitability with proxy earning per share have relation and influence significant to company value with proxy stocks market value at PT Timah Tbk by significant level 0,0158 but at PT Tambang Bukit Asam Tbk not haves relation and influence significant by significant level 0.4805 , Caused by factor external like unfavourable economy condition. (c) Last dividend policy with proxy dividend share and profitability with proxy earning per share in simultaneous have relation and influence to company value with proxy stocks market value at PT Timah Tbk by significant level 0,0635, but not have relation and influence significant PT Tambang Bukit Asam Tbk by significant level 0,1341, caused by factor external like unfavourable economy condition.Key word: dividend policy, profitability and company value